Islamic Will and Estate Management: A Case Study of Luweero District, Uganda - Khamis, Lubega Twaha (European Journal of Applied Sciences, 2025)
This study explores the practices of Islamic will and estate management in Luweero District, Uganda, aiming to understand how Islamic principles influence the administration of estates among Muslim communities. The research employed a qualitative methodology, including interviews with local community leaders, legal practitioners, and family members involved in estate management. Key findings reveal that while Islamic will are widely respected, there are challenges in aligning local customary laws with Islamic practices. The lack of awareness about Islamic estate management and limited access to legal frameworks further complicate the situation. Additionally, the study identifies successful community initiatives aimed at educating Muslims about their rights and obligations under Islamic law. These findings underscore the importance of integrating Islamic principles into local estate management practices and highlight the need for community- based legal education to ensure equitable estate distribution in the context of Islamic law.